An investigation of college and university foodservice administrators' perceptions of food waste reduction activities and food waste disposal methods - Kwon, Sockju; Bednar, Carolyn; Kwon, Junehee; Bush, Rose (My University, 2011)
This study was designed to investigate foodservice administrators’ perceptions regarding food waste management (FWM) in college and university foodservice operations. Research methods included focus groups and a national survey. The survey questionnaire was developed based on focus groups and validated and pilot‐tested before posting online. Sixty‐three voting delegates of the National Association of College and University Food Services completed the survey. Educating customers about FWM and composting were selected as most likely to reduce food waste among food waste reduction activities and among food disposal methods, respectively. Results varied depending on management types, operation types, and information source about FWM.
Keywords: Food waste management; College and university foodservice operations; Composting; Food waste disposal